Identifying Flood Hazard Potentials Based on Geographical Characteristics in the Jaffna District, Sri Lanka: Identifikasi Potensi Bencana Banjir Berdasarkan Ciri-ciri Geografi di Daerah Jaffna, Sri Lanka - Piratheeparajah, Nagamuthu; Chan, Ngai Weng; Tan, Mou Leong (GEOGRAFI, 2020)
Floods is a major hazard causing property damage, business and tourism loss, crop damage and negative effects on people in the Jaffna District of Sri Lanka. This study was conducted to identify the geographical characteristics that contribute to flood hazard potentials in the study area.  Primary data was collected using focus group discussion and field visits, with data from government departments. Data were analyzed using the descriptive statistical method, and the results were mapped using ARC GIS 11.2 software. Rainfall variability, especially intensity, directly affects flood impacts. The geographical terrain of a place, whether low-lying, flat or in the form of depression has high flood potentials. The study revealed that 26% of the low elevation places of the district have experienced severe flooding during the last sixty years. Other geographical characteristics such as soil types, collapsed natural and human-made drainage systems, unplanned road development, railway track construction, and siltation of ponds are also found to contribute to the flood hazards. After identifying the geographical characteristics and flood potentials, the flood-prone areas can be mapped and appropriate flood-alleviation measures put into place.